2018
DOI: 10.20884/1.jap.2017.19.2.597
|View full text |Cite
|
Sign up to set email alerts
|

g.640T>C Polymorphism of the TGF-β2 Gene is Associated with Salmonella pullorum Resistance in Indonesian Chickens

Abstract: The objectives of this study were to identify polymorphism of transforming growth factor β2 (TGF-β2) gene associated with Salmonella pullorum resistance in Indonesian chickens. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assays were used to genotype Indonesian chickens. Analysis of polymorphism was conducted by using PopGen 3.2 software. The effect of genotype on S. pullorum resistance was analyzed using the SAS General Linear Model (GLM) procedure. Genotyping was performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Polymerase chain reaction (PCR) amplified a partial region of the TGF-β2 gene, which showed a molecular weight of 284 bp (Figure 2). The present results agree with other authors (21)(22)(23).…”
Section: Pcr Assaysupporting
confidence: 94%
See 3 more Smart Citations
“…Polymerase chain reaction (PCR) amplified a partial region of the TGF-β2 gene, which showed a molecular weight of 284 bp (Figure 2). The present results agree with other authors (21)(22)(23).…”
Section: Pcr Assaysupporting
confidence: 94%
“…It was reported that chickens had two alleles (T and C) and three genotype variants (TT, CT, and CC) for the TGF-β2 gene (21). Polymorphic Indonesian chickens with two alleles (T and C) and three genotypes (TT, CT, and CC) were seen by (23). At the same time, the T allele had a higher prevalence than the C allele in Indonesian chickens owing to inbreeding and vigorous selection of the TGF-β2 gene.…”
Section: Distribution Of Genotype and Allele Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle growth in livestock is influenced by three main hormones namely steroids, transforming growth factor-beta (TGF-β), and myostatin (Dayton & White 2007). TGF-β is a family of growth factor hormones that regulate biological activity in a very broad range such as morphogenesis (Lorda-Diez et al 2010), development (Lu et al 2013), production (Jin et al 2013), reproduction (Gu et al 2017), and disease resistance (Muhsinin et al 2017). A previous study by Li et al (2003) showed that TGF-β3 plays a dominant role in growth, especially body weight and average daily gain (ADG).…”
Section: Introductionmentioning
confidence: 99%